Comparison of energy scenario alternatives for Chile: Towards low-carbon energy transition by 2030. (1st September 2020) - Simsek, Yeliz; Sahin, Hasret; Lorca, Álvaro; Santika, Wayan G.; Urmee, Tania; Escobar, Rodrigo
Abstract: The objective of the paper is to generate an energy and environmental model using LEAP to forecast energy demand, supply, emissions for Chile by 2030 and create scenarios considering different policies motivated by current policy as well as national and international commitments from Chile. This paper contributes to literature by developing a long-term energy plan including all sectors for Chile, describing energy scenario alternatives and analyzing current policy, nationally determined contributions and sustainable development goals. Results indicate that scenarios with significant energy demand reduction for all sectors showed considerable emission reduction by 2030. In all scenarios, demand sector showed major contribution to emissions when compared to transformation sector. Although emissions from transformation sector demonstrate significant reduction by 2030, decrease in demand side is not clearly noticed for some scenarios. Chile requires appropriate energy efficiency and renewable energy policies for demand sides of sectors especially transport, mining and other industries to reduce emissions at demand-side as having decarbonization for transformation side. Scenarios including more wind, PVsolar, CSPsolar and hydropower plants reached more than 80% renewable electricity generation by 2030. Thus, cleaner production portfolio which results in fewer emissions and more diversification in terms of energy generation can be established in Chile. Highlights: Scenarios with energy demand reduction showed considerable emission reduction by 2030. In all scenarios, demand sector showed major contribution to emissions. Emissions from transformation sector demonstrate significant reduction by 2030. Chile requires appropriate energy efficiency, renewable energy policies for demand side. 80% renewable electricity generation is reached including more renewables by 2030.